TANTANGAN DALAM PENERAPAN AKUNTANSI MUSYARAKAH DI INDONESIA - Nassa Abyan Mufid; Ilham Pratama Setiawan; Muhammad Hafidz Abilla; Muhammad Abi Fauzi Syariffudin; Mukhlishotul Jannah (Cahaya Ilmu Bangsa, 2024)
The implementation of musyarakah accounting in Indonesia faces various challenges, especially in the lack of uniform accounting standards, limited competent human resources, and the complexity of transactions involving assets and profit sharing schemes. This research aims to identify these challenges through a qualitative approach and case studies on Islamic financial institutions. The research results show that the lack of harmonization of accounting standards, public awareness, and technology integration are the main obstacles in the implementation of musyarakah accounting. The proposed solutions include the development of globally recognized sharia accounting standards, increasing human resource competence, intensive socialization, and the use of technology. The implementation of the Musyarakah Mutanaqisah (MMQ) scheme in sharia banking financing shows the advantages of joint ownership and a profit sharing system, even though it faces risks related to transaction costs and taxes. Integrated strategic efforts are needed to optimize the implementation of musyarakah accounting to support the growth of the sharia financial industry in Indonesia.